Boosting Students’ Speaking Skills through Peer-Assessment - Carriel Armijos, Daniel Francisco (2022)
It is concluded that for the first question, the innovation works well for university students. As the research findings in this innovation prove the significance of peerassessment in promoting learners’ performance, it seems beneficial to incorporate it into EFL classes in general. At first, it was anticipated that this academic strategy would boost students´ speaking skills and subskills for university students in their second level. S2 also got 8 and in the end got 15 out of 15 itself giving full credit to the innovation being in this case applied for the Speaking improvement for A2 level students. Besides, this type of assessment would create stronger bonds with people with different cultural, religious backgrounds. All in all, it is concluded that the innovation project made a real change for the better.